1987
DOI: 10.1159/000457744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics in Pregnancy and Perinatology

Abstract: Ampicillin has been most thoroughly studied in regard to placental transfer. Both during the first/second trimester and at term, fetal drug levels rose slowly to reach values similar to those in the maternal circulation 1-3 h after maternal drug administration; thereafter, fetal drug levels exceeded corresponding maternal values. Amniotic fluid levels were low during early gestational periods; during late gestation these levels were significant and even exceeded corresponding maternal values 6-8 h after drug a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Increased free fractions have been reported for theophylline, salicylic acid, digoxin, phenylbutazone, phenytoin, phenobarbitone, clonazepam, carbamazepine and various analgesic compounds (Aranda et al 1976;Bourgeois & Dodson 1983;Fredholm et al 1975;Gorodischer et al 1974;Groce et al 1985;Kuhnz et al 1984;Kurz et al 1977a,b;Meuldermans et al 1986;Nau 1985;Pacifici et al 1984;Wallin & Herngren 1985;Windorfer et al 1974;Yaffe & Stem 1976).…”
Section: Neonatesmentioning
confidence: 98%
“…Increased free fractions have been reported for theophylline, salicylic acid, digoxin, phenylbutazone, phenytoin, phenobarbitone, clonazepam, carbamazepine and various analgesic compounds (Aranda et al 1976;Bourgeois & Dodson 1983;Fredholm et al 1975;Gorodischer et al 1974;Groce et al 1985;Kuhnz et al 1984;Kurz et al 1977a,b;Meuldermans et al 1986;Nau 1985;Pacifici et al 1984;Wallin & Herngren 1985;Windorfer et al 1974;Yaffe & Stem 1976).…”
Section: Neonatesmentioning
confidence: 98%
“…Since the pH in the fetus is slightly lower than the maternal plasma, the fetal-maternal concentration ratio for weakly basic drugs may be greater for the free drug than the total drug. Nau (1985) made estimations of fetal-maternal ratios for free and total drug concentrations based on formulae derived from the Henderson-Hasselbach equation (for basic drugs): where Ctr = concentration of free drug in the fetus; Cfm = maternal free drug concentration; Ctotf = total drug concentration in the fetus; Cwtm = maternal total drug concentration; fu = fraction unbound.…”
Section: Ph Gradientmentioning
confidence: 99%
“…Assuming protein binding of 34% (0.66 unbound fraction) in the fetus and 63% (0.37 unbound fraction) in the maternal plasma, the free fetal-maternal ratio may be 1.4 while the fetal-maternal concentration ratio of total drug may be predicted at 0.8. However, due to the pH dependence of protein 266 binding, free drug concentrations of lignocaine cannot be predicted from total drug concentrations (Nau 1985). Several authors have reported higher fetal lignocaine concentrations in association with fetal acidosis (Biehl 1978;Brown 1976;Petrie 1974).…”
Section: Ph Gradientmentioning
confidence: 99%
“…A possible re-equilibration of the drug from the fetal to the maternal compartment could offer an explanation for the longer maternal elimination half-life, observed for CFT during pregnancy. Similarly to CFT, after the intramuscular administration of ampicillin (pK a = 2.5) fetal drug levels were initially found to be lower and then exceeded the corresponding maternal ones, with drug levels decreasing at a slower rate in the fetal blood than the maternal one [29] .…”
Section: Discussionmentioning
confidence: 95%